PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN JASA TRANSPORTASI KERETA API INDONESIA (KAI) DAERAH OPERASI 6 YOGYAKARTA - Veronica Diona Mahardhika. K; Supriyono . (STIE AUB Surakarta, 2016)
The research aims are know the influence of service excellence toward consumers satisfaction of train transfortation users Yogyakarta area 6.The sample in this research are train passengers.The sampling method is using simple random sampling. From this method, the sample was taken of 100 respondents. Data analysis method used the research instrument to test the validity, reliability, classical assumptions, and multiple linear regression with t test, F test, and test the coefficient of determination (R2). Result are all valid questions item and reliable research instruments. The results of multiple regression analysis yields a relationship that assurance is a variable that has the greatest regression coefficient. T test results showed that the variable tangible, assurance, empathy partial effect on passenger satisfaction. While variable reliability, and responsiveness not partial effect on passenger satisfaction. The F test results showed that the variable tangible, reliability, responsiveness, assurance, empathy influence simultaneously toward passenger satisfaction.The results showed 55.8% of passenger satisfaction variable variation can be explained by the variable tangible, reliability, responsiveness, assurance, empathy. While the remaining 44.2% is influenced by other factors not examined. Keywords: quality of service, tangible, reliability, responsiveness, assurance, empathy, passenger satisfaction